Can bacteria and carbon-based nanomaterials revolutionize nanoremediation strategies for industrial effluents? - de Carvalho Lima, Elidamar Nunes; Souza, Luiz Henrique Mesquita; Aguiar, Eduardo Martins; Octaviano, Ana Luiza Moraes; Justo, João Francisco; Piqueira, José Roberto Castilho (Frontiers in Nanotechnology, 2024)
In this study, we delved into cutting-edge strategies for the effective management of wastewater, a critical issue exacerbated by industrial pollution and urban expansion. We introduce the use of carbon-based nanomaterials (CBNs), either alone or functionalized with bacteria, as a novel nanobiotechnological solution for urgent nanobioremediation needs. This technique is notable for its exceptional ability to remove various industrial pollutants, including heavy metals, pesticides, textiles, and dyes, emphasizing the pivotal role of CBNs. The development of bionanocomposites through the integration of CBNs with bacteria represents a significant advancement in enhancing bioremediation efforts. In this study, we assessed the potential health and environmental risks associated with CBN usage while offering an in-depth evaluation of the adsorption mechanisms and factors influencing bioremediation effectiveness. Furthermore, the improved efficiency in treating industrial effluents facilitated by bionanocomposites was investigated, and their alignment with circular economy principles through recyclability is discussed. We aimed to provide, a detailed overview of recent advancements, challenges, and prospects for CBNs and bacterial application in sophisticated wastewater treatment, underscoring their vital importance in promoting the environment.